Integrative Nursing and Optical Approaches to Vision Rehabilitation: Best Practices in Prescribing Corrective Lenses for Pseudophakic Patients - Misky, Dina Idarous; Nourah Abdullah Alowais ,; Fawaz Nasser Alhuwaymil,; Fatimah Fahad Alnasser,; Reem Hilal Break Al-Otaibi,; Iyman Ahmed Mohamad Harash,; Mona Dakheil Saad Albalawi ,; Hadi Mohmmed Mohsen Hagawi ,; Abdulrahman Saad Bijad Alsubaie,; Maryam Essa Ayyashi,; Shouhrah Saad Mohumad Alshoumrani,; Abdulrahman Mohsen Siddiq Tubayqi,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Cataract surgery, one of the most common procedures worldwide, replaces the opacified crystalline lens with an intraocular lens (IOL), creating a pseudophakic eye. Despite advanced IOL technology, a significant proportion of patients require spectacle correction postoperatively to achieve optimal visual acuity and comfort for specific tasks, making precise refraction and spectacle prescribing a critical component of visual rehabilitation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to outline best practices for prescribing corrective lenses for pseudophakic patients, integrating surgical outcomes with patient-specific visual needs. It emphasizes an interdisciplinary approach to navigate the unique challenges of pseudophakia, including managing residual refractive error, anisometropia between staged surgeries, and the specific demands of premium IOLs. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of the prescribing process is presented, covering the timing of postoperative refraction, the indications for spectacles, and the necessary diagnostic equipment (e.g., autorefractor, phoropter, corneal topographer). The analysis details how to tailor prescriptions based on IOL type (monofocal, toric, multifocal, EDOF) and patient lifestyle, including the selection of progressive addition lenses, occupational designs, and specialized coatings. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Successful visual rehabilitation depends on accurate refraction performed after ocular stabilization (typically 3-4 weeks post-surgery). Key to patient satisfaction is managing interim anisometropia, correcting even small residual errors, and prescribing task-specific eyewear. A coordinated effort between ophthalmologists, optometrists, and opticians is essential to translate surgical results into functional, comfortable vision. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Prescribing spectacles for pseudophakic patients is a nuanced, rehabilitative process rather than a simple transaction. A patient-centered, interdisciplinary approach ensures that spectacles effectively complement the surgical outcome, maximizing visual quality, binocular comfort, and long-term satisfaction.